Controlling Mirror Symmetry Breaking and Network Formation in Liquid Crystalline Cubic, Isotropic Liquid and Crystalline Phases of Benzil‐Based Polycatenars. Issue 68 (29th October 2020) - Reppe, Tino; Poppe, Silvio; Tschierske, Carsten
Abstract: Spontaneous development of chirality in systems composed of achiral molecules is important for new routes to asymmetric synthesis, chiral superstructures and materials, as well as for the understanding of the mechanisms of emergence of prebiotic chirality. Herein, it is shown that the 4, 4′‐diphenylbenzil unit is a universal transiently chiral bent building block for the design of multi‐chained (polycatenar) rod‐like molecules capable of forming a wide variety of helically twisted network structures in the liquid, the liquid crystalline (LC) and the crystalline state. Single polar substituents at the apex of tricatenar molecules support the formation of the achiral (racemic) cubic double network phase with Ia 3 ‾ d symmetry and relatively small twist along the networks. The combination of an alkyl chain with fluorine substitution leads to the homogeneously chiral triple network phase with I 23 space group, and in addition, provides a mirror symmetry broken liquid. Replacing F by Cl or Br further increases the twist, leading to a short pitch double gyroid Ia 3 ‾ d phase, which is achiral again. The effects of the structural variations on the network structures, either leading to achiral phases or chiral conglomerates are analyzed. Abstract : Soft helical networks : Achiral benzil‐based multi‐chained molecules form a series of spontaneously mirror‐symmetry‐broken soft matter structures; the steric and electronic effects of polar substituents on helical self‐assembly, local and long range network formation as well as through‐space interhelical interactions are discussed.